A Delta Operator Approach for the Discrete-Time Active Disturbance Rejection Control on Induction Motors. (24th November 2013) - Cortés-Romero, John; Luviano-Juárez, Alberto; Sira-Ramírez, Hebertt
Abstract : The problem of active disturbance rejection control of induction motors is tackled by means of a generalized PI observer based discrete-time control, using the delta operator approach as the methodology of analyzing the sampled time process. In this scheme, model uncertainties and external disturbances are included in a general additive disturbance input which is to be online estimated and subsequently rejected via the controller actions. The observer carries out the disturbance estimation, thus reducing the complexity of the controller design. The controller efficiency is tested via some experimental results, performing a trajectory tracking task under load variations.